Identification of gas reservoirs and determination of their parameters by the combination of radioactive logging methods - V. V. Kulyk; M. S. Bondarenko (Геофизический журнал, 2016)
The paper proposes a new approach for using of combination of radioactivity logging, which allows determining a set of gas reservoir parameters (nature of saturation, true porosity, gas saturation coefficient) taking into account influence of the pressure and temperature conditions of occurrence. Analysis of the ways of averaging the neutron-apparent porosity and the density-apparent porosity for obtaining the true porosity was made. Method of determination of gas saturation, which uses the same combination of radioactivity logging as in determining the true porosity of gas reservoirs, was developed. The results presented in the paper, were obtained over a wide range of depth (up to 10 km). Application of developed approaches for determination of petro-physical parameters of gas reservoirs is demonstrated by the example of cased coalbed methane well.